2006
DOI: 10.1063/1.2358328
|View full text |Cite
|
Sign up to set email alerts
|

Cs Eu Br 3 : Crystal structure and its role in the photostimulation of CsBr:Eu2+

Abstract: Structure and photostimulated luminescent properties of Eu-doped M 2 Ba X 4 ( M = Cs , Rb; X = Br , Cl) CsBr: Eu 2+ has recently been investigated as a photostimulable x-ray storage phosphor with great potential for application in high-resolution image plates. In a recent paper Hackenschmied et al. ͓J. Appl. Phys. 93, 5109 ͑2003͔͒ suggested that segregations of CsEuBr 3 or Cs 4 EuBr 6 formed within CsBr: Eu 2+ during annealing are responsible for an increase in the photostimulated luminescence ͑PSL͒ yield. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 12 publications
6
30
0
Order By: Relevance
“…It is found that MA and FA are able to stabilize the PVSK, while other cations with similar size, such as CH 3 CH 2 NH 3 + , [29] (CH 3 ) 2 NH 2 + , [30] would form a non-PVSK structure. Compared to their oxide counterparts, the less negative charge and larger ionic size of halides only allows for B site metal cations to be selected from a few elements, including the alkaline earth, [31] bivalent rare earths, [32] and group 14 elements (Pb 2+ , Sn 2+ , Ge 2+ ). [33,34] 6 ] 4− octahedra.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that MA and FA are able to stabilize the PVSK, while other cations with similar size, such as CH 3 CH 2 NH 3 + , [29] (CH 3 ) 2 NH 2 + , [30] would form a non-PVSK structure. Compared to their oxide counterparts, the less negative charge and larger ionic size of halides only allows for B site metal cations to be selected from a few elements, including the alkaline earth, [31] bivalent rare earths, [32] and group 14 elements (Pb 2+ , Sn 2+ , Ge 2+ ). [33,34] 6 ] 4− octahedra.…”
Section: Introductionmentioning
confidence: 99%
“…These additional peaks could not be identified through the ICDD database. Maybe, they are attributed to the degradation of CsEuBr 3 phases as reported by Hesse et al [6,7]. Fig.…”
Section: Characterizationmentioning
confidence: 76%
“…The hydrogen atoms are located interstitially at the face-centered sites in the bcc CsBr lattice, which is detrimental to the transformation from Eu-Vc s IDC to CsEuBr 3 AC. Hesse et al [6] reported that the emission peaks of Eu 2+ (5d 6 -4f 7 ) are at 440 and 452 nm in CsBr and CsEuBr 3 . Hence, we suppose that the red shift is due to an increasing number of CsEuBr 3 AC.…”
Section: Article In Pressmentioning
confidence: 98%
See 2 more Smart Citations